1998
DOI: 10.1023/a:1001791509073
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pulsed field gel electrophoresis of restriction endonuclease digested genomic DNA from a collection of clinical isolates of Rhodococcus equi was used to compare strain diversity on different Thoroughbred horse farms over time. Restricted diversity was found among the isolates tested, as the same strains were detected on multiple farms and in multiple years. Marked variation occurred in strain prevalence with some strains being represented by single isolates, and the most prevalent by 26 isolates. There were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several genotypically distinct isolates of R. equi have been obtained from soil, air, water, and feces at horse breeding farms [12, 13], but the majority of studies to date have been conducted using a few relatively well characterized strains [2, 7, 14, 15]. The advantage to this approach is reproducibility among studies and the ability to build on previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Several genotypically distinct isolates of R. equi have been obtained from soil, air, water, and feces at horse breeding farms [12, 13], but the majority of studies to date have been conducted using a few relatively well characterized strains [2, 7, 14, 15]. The advantage to this approach is reproducibility among studies and the ability to build on previous work.…”
Section: Introductionmentioning
confidence: 99%
“…During the study we detected chromosomal variability among some of investigated isolates what had been previously described even among isolates collected from the same farm [ 26 , 33 , 34 ]. However, these studies were performed on a high number of isolates from heterogeneous horse populations with numerous clinical cases and soil samples from many farms contrary to our study conducted on smaller farms that stay in contact, for example by exchange of the horses.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are similar to the genotypic diversity of R equi isolates from Australia. 22,23 Guidelines for molecular epidemiologic characterization of strains by use of PFGE indicate that strain characterization should only be applied to small sets of isolates related to potential outbreaks. 28 In the study reported here, isolates from the same farm met these criteria for strain characterization.…”
Section: Discussionmentioning
confidence: 99%
“…19 Serologic groupings and examination of plasmid patterns, however, are not as discriminating as genetic fingerprinting (genotyping) techniques such as pulsed-field gel electrophoresis (PFGE) of restriction endonuclease-digested genomic DNA. 20 In a few studies, [21][22][23] investigators have used PFGE to evaluate isolates of R equi obtained from horses. Differences in PFGE patterns among 21 European isolates of R equi from feces of healthy cattle and horses have been documented as well as variability within and among farms.…”
mentioning
confidence: 99%
See 1 more Smart Citation